Design of an injection mold with local placement of heating coatings for warpage compensation (2024)
The influence of the thermal injection mold design crucially affects the geometric precision of injection molded parts. However, the adjustability of the heat flux distribution established with the conventionally used cooling channels is limited and cannot cover the vari able cooling demand. The proposed approach of using heating coatings on the cavity surface to manipulate the part’s cooling rate shows that it may be advantageous, due to the close and localized application to the part. A simulative optimization routine determines the necessary position and surface power of the heating coating. The objective of this methodology is to homogenize the surface temperature, inner cooling rate, and freeze time inside the part. This work applies the simulative design method for the optimized placement and heating power on a mold for a three-dimensional part. As the temperature field of the heating coating depends on the contacting, the electro-thermal simulation is analyzed and confirmed as sufficient to establish the optimal heat flux distribution. A process simulation study shows the dimension with the most critical warpage is decreased by 90%.